Are College Students More Likely to Be Food Insecure than Nonstudents of Similar Ages?. Issue 4 (16th October 2020) - Gundersen, Craig
Abstract: "College hunger" has received a great deal of attention in the media and on some campuses across the US. In this article, I consider the question: Are college students more likely to be food insecure than those of similar ages who are not in college? To answer this question, I use data from the 2014 to 2018 Current Population Survey (CPS), the data used for the official food insecurity rates in the US. Across many specifications, I find zero evidence that college students are at higher risk of food insecurity than nonstudents. This holds whether one looks at those between the ages of eighteen and twenty‐five or between twenty‐six and thirty; whether one looks at "person is a child of the respondent" or "person is not a child of the respondent"; or whether one looks at demographic categories. In fact, food insecurity rates are up to twice as high among nonstudents in comparison to full‐time college students. Abstract : Related Content: School meals and quality of household food acquisitions Related Content: Did state-mandated restrictions on sugar-sweetened drinks in California high schools increase soda purchases in school neighborhoods? Related Content: Did the New School Meal Standards Improve the Overall Quality of Children's Diets?